2017
DOI: 10.5657/kfas.2017.0085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sargassum serratifolium Extracts on β-Amyloid Production

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder of insidious onset that causes gradual loss of memory and cognitive function, and it is the most common form of dementia in the elderly. AD is characterized by neuritic plaques and neurofibrillary tangles in the brain, together with loss of neuronal cells. The major neuropathological hallmark of AD is the accumulation of extracellular neurotoxic β-amyloid (Aβ) peptides, such as Aβ1-42, in the brain. In the present study, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Heo et al [ 80 ] found that fucoxanthin isolated from S. siliquastrum at concentrations of 5–200 µM reduced the toxicity induced by H 2 O 2 in Vero cells, while Alghazwi et al [ 79 ] suggested that pretreatment with fucoxanthin (0.1–2 µM) increased the survival rate of cells damaged by Aβ 25–35 up to 67–98.5%. Choi et al [ 81 ] also indicated that an alcohol extract of S. serratifoilum reduced the accumulation of Aβ 1–42 in Chinese hamster ovary cells (CHO-751 cells). Our results ( Figure 3 and Figure 4 ) correspond with the statement that concentrations of the tested sample likely depend on cell lines, and some cell lines, such as PC-12 cells, are more sensitive than others.…”
Section: Discussionmentioning
confidence: 99%
“…Heo et al [ 80 ] found that fucoxanthin isolated from S. siliquastrum at concentrations of 5–200 µM reduced the toxicity induced by H 2 O 2 in Vero cells, while Alghazwi et al [ 79 ] suggested that pretreatment with fucoxanthin (0.1–2 µM) increased the survival rate of cells damaged by Aβ 25–35 up to 67–98.5%. Choi et al [ 81 ] also indicated that an alcohol extract of S. serratifoilum reduced the accumulation of Aβ 1–42 in Chinese hamster ovary cells (CHO-751 cells). Our results ( Figure 3 and Figure 4 ) correspond with the statement that concentrations of the tested sample likely depend on cell lines, and some cell lines, such as PC-12 cells, are more sensitive than others.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of fucoxanthin was determined by nuclear magnetic resonance (NMR) spectra recorded on a Bruker Avance Neo 600 MHz spectrometer with CDCl 3 as solvent and TMS as internal standard. 1 H NMR spectra was measured at 600 MHz and 13 C was measured at 150 MHz at the Institute of Chemistry, Vietnam Academy of Science and Technology. The structure of fucoxanthin was determined by comparing the NMR data with the published standard (Yan et al 1999).…”
Section: Determination Of Fucoxanthin Structurementioning
confidence: 99%
“…Fucosterol from Padina australis was evaluated for its neuroprotective effects in SH-SY5Y cells treated with Aβ 25-35 ; activation of the down-regulation of amyloid precursor protein (APP) expression (Alghazwi et al, 2018). Choi et al (2017) also reported that ethanol extract of S. serratifoilum reduced the accumulation of β-amyloid (Aβ 1-42 ) in the cell line CHO-751 (Chinese hamster ovary cells). Our obtained results were also similar to the above statement.…”
Section: Protective Activity Against Cytotoxicity In Alzheimer's Dise...mentioning
confidence: 99%